Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Pyoe Pin, Myanmar - Christie, Angela; Green, Duncan (Itad, Oxfam and IDS, 2018)
This paper examines adaptive approaches in aid programming in a fragile, conflict and violence-affected setting (FCVAS), namely Myanmar. A combination of desk review and field research has been used to examine some of the assertions around the ‘adaptive management’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blue-print and linear project plans. This paper explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for promoting empowerment and accountability in such ‘messy places’. This case study focuses on Pyoe Pin (‘Young Shoots’), a DFID-funded, British Council managed governance programme, which has been running since 2007.
Keywords: A4EA; Adaptive Development; Economy; Fishery

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (IDS, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

Case study: Embedding reform and exiting: LASER’s application of the hourglass approach to achieve sustainable results - Manuel, Clare (DFID-LASER Programme, 2016)
This case study describes how LASER has gone about enabling systemic change and sustainable uptake of reforms that address complex institutional problems in Kenya, Rwanda, Sierra Leone, Somaliland and Uganda. In each of these countries LASER has designed-in a sustainable approach from the start based on: (i) local ownership and leadership of reforms based on developing country (rather than donor) priorities; (ii) use of country (rather than donor programme) systems; and (iii) an understanding that the role of the donor / development practitioner is to support (rather than buy) reform. The case study uses LASER’s hour glass methodology, illustrated with examples from LASER interventions, to show how these principles guide LASER operations every step of the way.
Keywords: IMPORTANT; Practice